2015
DOI: 10.1016/j.trd.2015.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wind strength and wave height on ship incident risk: Regional trends and seasonality

Abstract: a b s t r a c tOceanographic conditions like wind strength and wave height affect the risk of shipping incidents. Seasonal variations and trends in these effects are studied for weather-related incidents and pollution incidents, for six major ship types and for six regions across the globe. The employed database of more than five million observations combines information from various sources on oceanographic conditions, ship particulars, and incidents. The magnitude of wind and wave effects is found to vary by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…Analyses by Heij and Knapp (2015) showed that international shipping over the Indian Ocean is carried out using three types of ships: general cargo vessels (about 31.4%), containerships (about 22.4%), and oil tankers (about 24%). Containerships and oil tankers normally have a large gross tonnage over 50 K, while general cargo vessels have a small tonnage ranging about 5 -20 K. They also showed that the ratio for weather-related incidents is about 0.3% for general cargo vessels and only 0.02% for containerships sailing across the Indian Oceans.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses by Heij and Knapp (2015) showed that international shipping over the Indian Ocean is carried out using three types of ships: general cargo vessels (about 31.4%), containerships (about 22.4%), and oil tankers (about 24%). Containerships and oil tankers normally have a large gross tonnage over 50 K, while general cargo vessels have a small tonnage ranging about 5 -20 K. They also showed that the ratio for weather-related incidents is about 0.3% for general cargo vessels and only 0.02% for containerships sailing across the Indian Oceans.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, quantitative maritime risk assessment has been studied and a lot of practices have been performed in many research, as described by Li, Meng, and Qu (2012). These mainly include correlation analysis (Eliopoulou, Papanikolaou, & Voulgarellis, 2016), logistic regression (Jin & Thunberg, 2005; Jin, Kite‐Powell, Thunberg, Solow, & Talley, 2002), zero‐truncated binomial regression (Weng & Yang, 2015), negative binary regression (Heij & Knapp, 2015), data clustering (Kim, Park, & Jung, 2017), Bayesian approach (Hassel, Asbjørnslett, & Hole, 2011), Bayesian Belief Networks (BBN) (Antão, Guedes Soares, Grande, & Trucco, 2009; Yang et al., 2018; Zhang et al., 2016, Wan, Yan, Zhang, Qu, & Yang, 2019, Antão & Guedes Soares, 2019; Zhang, Yan, Yang, Wall, & Wang, 2013), and evidence reasoning (ER) or belief rule base (BRB) (Balmat et al., 2009; Yang, Wang, Bonsall, & Fang, 2010; Zhang et al., 2016; Zhang, Yan, Zhang, Haugen, & Yang, 2014; Zhang, Yan, Zhang, Yang, & Wang, 2016). Moreover, some studies made accident data analysis by combining different approaches (Li, Yin, Bang, Yang, & Wang, 2014; Mullai & Paulsson, 2011; Tirunagari, Hänninen, Ståhlberg, & Kujala, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The rating measures both safety and environmental hazards. The process is based on information published by a plethora of sources such as PSC deficiencies, casualties, and vetting inspections [15]. However, the methodology used for rating is not available to the public.…”
Section: Introductionmentioning
confidence: 99%